Strontium Substitution for Calcium in Lithogenesis - Blaschko, Sarah D. (2012)
PURPOSE: Strontium has chemical similarity to calcium, which enables the replacement of calcium by strontium in biomineralization processes. Incorporating strontium into human bone and teeth has been studied extensively but little research has been performed of the incorporation of strontium into urinary calculi. We used synchrotron based x-ray fluorescence and x-ray absorption techniques to examine the presence of strontium in different types of human kidney stones. MATERIALS AND METHODS: Multiple unique human stone samples were obtained via consecutive percutaneous nephrolithotomies/ureteroscopies. A portion of each stone was sent for standard laboratory analysis and a portion was retained for x-ray fluorescence and x-ray absorption measurements. X-ray fluorescence and x-ray absorption measurements determined the presence, spatial distribution and speciation of strontium in each stone sample. RESULTS: Traditional kidney stone analyses identified calcium oxalate, calcium phosphate, uric acid and cystine stones. X-ray fluorescence measurements identified strontium in all stone types except pure cystine. X-ray fluorescence elemental mapping of the samples revealed co-localization of calcium and strontium. X-ray absorption measurements of the calcium phosphate stone showed strontium predominately present as strontium apatite. CONCLUSIONS: Advanced x-ray fluorescence imaging identified strontium in all calcium based stones, present as strontium apatite. This finding may be critical since apatite is thought to be the initial nidus for calcium stone formation. Strontium is not identified by standard laboratory stone analyses. Its substitution for calcium can be reliably identified in stones from multiple calcium based stone formers, which may offer opportunities to gain insight into early events in lithogenesis.